The role of multiple-stakeholder engagement in water security in Shakadza community, Limpopo Province, South Africa - Rankoana, Sejabaledi A. (Technium Social Sciences Journal, 2021)
Shakadza community falls within one of the areas experiencing intermittent drought in Limpopo Province, South Africa where about 300 households depend on a common groundwater resource that rests on rainfall for recharge. An exploratory study was conducted in this community to examine the roles of different stakeholders to ensure daily water supply. Data collected through semi-structured interviews and focus group discussions show that unpredictable rainfall has led to inconsistent water supply from the main groundwater resource in the community. However, a regular supply of water for household consumption is satisfied through a multi-stakeholder intervention in which the municipality provides daily water supply to the community, the pump operators monitor the reservoir levels while the water committee monitors the use of stand-pipes. In this way, government officials as the water authorities, the water committee and pump operators as the community water resource managers, play joint roles to ensure reliable water supply in the community. Therefore, the multi-stakeholder roles include daily delivery of water to the reservoir, consistent check of the reservoir water level, monitoring of the water uses, prevention of tap leakages, barring of livestock drinking and washing from the taps, and water connections for gardening. These stakeholders manage water supply with different, and sometimes complementary roles and objectives. The water resource management practices can be recommended to add value to the climate change adaptation efforts to sustain water provision in the Limpopo Province. This type of a community-based intervention could be used as an essential element in climate adaptation practices to sustain the livelihood of communities negatively impacted by climate change